Analisis kesalahan struktur kalimat dasar pada keterampilan menulis teks wawancara peserta didik kelas iv sekolah dasar negeri tegalsari tahun pelajaran 2021/2022 - Puspawati, Yunita Dwi; Slamet, St Y; Surya, Anesa (Universitas Sebelas Maret, 2022)
This study aims to describe the ability to use sentences based on sentence structure on the skills of writing interview texts for fourth grade students of SD Negeri Tegalsari. This research is a descriptive qualitative research with reports on the results of student interviews. The sampling technique in this research is the research subject. Data collection techniques used interviews, documentation studies, and observation. Validity test data using source triangulation techniques and triangulation techniques. The data analysis technique uses imperative analysis which includes four stages, namely: (1) data collection, (2) data reduction, (3) data presentation, (4) drawing conclusions. The percentage of errors in the use of subject indicators (19.23%), predicate indicators (13.46%), object indicators (8.65%), information indicators (45.2%), and complementary indicators (13.46%). The causes of errors in the use of sentences based on sentence structure in the reports of student interviews include: (1) lack of understanding of students on the selection and use of appropriate sentences, (2) lack of application of strategies in teaching sentence structure by teachers. The teacher's effort to overcome this is by giving exercises to students so that students are accustomed to communicating using standard language, both spoken and written.